PROFITABILITAS DAN EVALUASI KINERJA PRODUK AGROINDUSTRI RUMAH TANGGA GULA KELAPA KECAMATAN LAIS KABUPATEN BENGKULU UTARA PROVINSI BENGKULU - Fitri, Efa Yulita; Nusril, Nusril; Reswita, Reswita (Jurnal AGRISEP, 2019)
In the Home Industry of coconut sugar, the cost and profit calculation is still conventional. Profit calculation is needed in order to get the maximum profit of the business. The company's profit is related to cost, sales volume and selling price. One of the analytical tools that can be used is Cost Volume Profit (CVP) analysis. Profitability is a benchmark of the company's performance to generating the net income. The research aim to analyze the income, breakeven point, profitability ability and sensitivity, also analysing consumer perception about attribute level of importance and satisfaction of coconut sugar product in Dusun Hibrida, Pal 30 Village, Lais District, North Bengkulu Regency, Bengkulu Province. From sales of coconut sugar products amounted to Rp.60.183,47 per production. Which the profitability of coconut sugar products is 46%. If product performance exceeds the consumer expectations, they will feel satisfied. Importance Performance Analysis (IPA) is used to maping the relationship between importance and performance of each product attribute. The most important attributes and have good performance related to consumers is coconut sugar hygiene, taste, and food / beverages, coconut sugar color, durability, ease of accessing the product,  and coconut sugar solubility, that’s attributes need to be maintained.